Marketing of Sustainable Development in Educational Institutions of Ukraine in the Context of Cooperation with the EU (against the background of military circumstances) - Nataliia Mohylevska; Lesia Malooka; Kseniia Prykhodko (Socio-Cultural Management Journal, 2025)
Introduction. The armed conflict in Ukraine calls into question the achievements in sustainable development, environmental safety and international cooperation of European countries. Educational institutions are responsible for promoting sustainable development in all areas of their activities and society. Given Ukraine’s aspirations to integrate European standards of quality of life and implement the principles of sustainable development, it is of particular importance to study the long-term and successful experience of the European Union with its further adaptation to the national economic context. The purpose of the article is to identify sustainable development marketing initiatives in higher education institutions of Ukraine. The methodological basis of the study is the analytical and empirical principles, which involve synthesis, modelling, historical and logical analysis methods. The methodology is based on an empirical review of scientific developments on marketing issues and cultural initiatives for sustainable development. The results of the study confirm the hypothesis that marketing of an educational institution has a positive impact on sustainable development in the country. The scientific novelty of the research results is that this study contributes to the growth of the sustainability discourse in the academic community and provides practical recommendations for educational institutions seeking to improve their marketing strategies in line with environmental and social responsibility goals. This article contributes to the literature by expanding the understanding of sustainability marketing in higher education and providing practical recommendations for Ukrainian higher education institutions seeking to improve their marketing strategies in line with sustainability principles. The study highlights the link between sustainable marketing, student perceptions and the performance of higher education institutions. It aims to promote positive changes towards a more sustainable future in public higher education institutions.